The Other and the Reflection of Identity in Industrial Product Design (Journal of the College of Basic Education, 2025)
The research deals with the topic of (the other and the reflection of identity in industrial product design), including the research problem that By asking the following question: (Does the other play a role in designing industrial products according to a general cultural identity or Especially?), and the aim of the research was to identify the concept of the other in the industrial products designed And its reflection in the identity of the industrial product, while highlighting the importance of scientific and cognitive research . Research procedures and methodology, according to the descriptive scientific method in analysis, and one of the most important conclusions was that it formed Identity has a functional, aesthetic and interactive dimension in the other. One of the most important recommendations is that it is important to keep up with all technical, scientific and technological developments due to their importance in designing the other’s products.